2011
DOI: 10.1136/archdischild.2011.300162.63
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a specialised 'birth after caesarean section (BAC)' clinic

Abstract: Background Multiple caesarean sections (C/S) have an impact on maternal morbidity and are ‘resource hungry’. Previous audit data (April 2008–October 2009) in this unit had shown that 44% of elective C/S were performed for ‘maternal request’ after the woman had one previous C/S. Consequently a birth after caesarean (BAC) clinic was set up where the care of women was standardised. This is Consultant led with a specialised midwife and patient information leaflets. Aims To increase the percentage of women opting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Trials of decision‐support aids for women choosing mode of birth after a prior CS have shown that these may help women to feel more sure about their birth choice, but have demonstrated varied impacts on rates of VBAC . Local small‐scale evaluations of specialist consultant‐led and midwife‐led (V)BAC clinics to support women's decision‐making have shown mixed results in terms of increasing the proportion of women who choose VBAC or have a successful VBAC . More research is required to establish whether specialist VBAC clinics are effective in supporting women to achieve a vaginal birth following a prior CS in a setting where there is easy access to obstetric, anaesthetic and advanced neonatal support if needed.…”
Section: Discussionmentioning
confidence: 99%
“…Trials of decision‐support aids for women choosing mode of birth after a prior CS have shown that these may help women to feel more sure about their birth choice, but have demonstrated varied impacts on rates of VBAC . Local small‐scale evaluations of specialist consultant‐led and midwife‐led (V)BAC clinics to support women's decision‐making have shown mixed results in terms of increasing the proportion of women who choose VBAC or have a successful VBAC . More research is required to establish whether specialist VBAC clinics are effective in supporting women to achieve a vaginal birth following a prior CS in a setting where there is easy access to obstetric, anaesthetic and advanced neonatal support if needed.…”
Section: Discussionmentioning
confidence: 99%